c-Abl Activation Linked to Autophagy-Lysosomal Dysfunction Contributes to Neurological Impairment in Niemann-Pick Type A Disease - Marín, Tamara; Dulcey, Andrés E.; Campos, Fabián; de la Fuente, Catalina; Acuña, Mariana; Castro, Juan; Pinto, Claudio; Yañez, María José; Cortez, Cristian; McGrath, David W.; Sáez, Pablo J.; Gorshkov, Kirill; et al. (Frontiers in Cell and Developmental Biology, 2022)
Niemann-Pick type A (NPA) disease is a fatal lysosomal neurodegenerative disorder caused by the deficiency in acid sphingomyelinase (ASM) activity. NPA patients present a severe and progressive neurodegeneration starting at an early age. Currently, there is no effective treatment for this disease and NPA patients die between 2-3 years of age. NPA is characterized by an accumulation of sphingomyelin in lysosomes and dysfunction in the autophagy-lysosomal pathway. Recent studies show that c-Abl tyrosine kinase activity downregulates autophagy and the lysosomal pathway. Interestingly, this kinase is also activated in other lysosomal neurodegenerative disorders. Here, we describe that c-Abl activation contributes to the mechanisms of neuronal damage and death in NPA disease. Our data demonstrate that: (1) c-Abl is activated in in-vitro as well as in-vivo NPA models; (2) imatinib, a clinical c-Abl inhibitor, reduces autophagy-lysosomal pathway alterations, restores autophagy flux and lowers sphingomyelin accumulation in NPA patient fibroblasts and NPA neuronal models and (3) chronic treatment with nilotinib and neurotinib, two c-Abl inhibitors with differences in blood-brain barrier penetrance and target binding mode, show further benefits. While nilotinib treatment reduces neuronal death in cerebellum and improves locomotor functions, neurotinib decreases glial activation, neuronal disorganization and loss in hippocampus and cortex, as well as the cognitive decline of NPA mice. Our results support the participation of c-Abl signaling in NPA neurodegeneration and autophagy-lysosomal alterations, supporting the potential use of c-Abl inhibitors for clinical treatment of NPA patients.